10
$\begingroup$

Variation of my recent post. Strangely it leads to the result in term of Euler's constant;$\gamma$

Prove that

$$\int_{0}^{1}\int_{0}^{1}\left({x\over 1-xy}\cdot{\ln{x}-\ln{y}\over \ln{x}+\ln{y}}\right)\mathrm dx\mathrm dy=1-2\gamma$$

Where $\gamma=0.577215...$;Euler's constant.

My try:

$u=xy$ then $du=ydx$

$$\int_{0}^{1}\int_{0}^{y}{{u\over y^2}\over 1-u}\cdot{\ln{u\over y^2}\over \ln{u}}\mathrm du\mathrm dy$$

I can't understand how to or even glimsely to solve double integrals.

Any chance can someone show me a detail of the answer. Thank you.

$\endgroup$
3
  • $\begingroup$ the proposed approach in the other question doesn't work? $\endgroup$
    – tired
    Jan 3, 2017 at 11:19
  • 1
    $\begingroup$ Changing the order of integration we get $$ \int_0^1du\frac{u}{1-u}\int_u^1dv\frac{1}{v^2}\left(1-2\frac{\log(v)}{\log(u)}\right) $$ the inner integral is straightforward and you only need integral representation 5 from here en.wikipedia.org/wiki/… $\endgroup$
    – tired
    Jan 3, 2017 at 11:27
  • $\begingroup$ For a proof of different integral reps of Euler's constant see here: math.stackexchange.com/questions/980593/… $\endgroup$
    – tired
    Jan 3, 2017 at 11:41

2 Answers 2

10
+50
$\begingroup$

Folllowing @tired Comment(s): $$ \begin{align} \text{Let} &\colon\space x\,y=u,\,\,y=v \space\Rightarrow\space x/y=u/v^2,\,\,y\,dx=du,\,\,dy=dv \\[3mm] \color{red}{I} &= \int_{0}^{1}\int_{0}^{1}\left(\frac{x}{1-x\,y}\,\frac{\log{x}-\log{y}}{\log{x}+\log{y}}\right)\,dx\,dy = \int_{0}^{1}\int_{0}^{1}\left(\frac{(x/y)}{1-(x\,y)}\,\frac{\log{(x/y)}}{\log{(x\,y)}}\right)\,(y\,dx)\,dy \\[3mm] &= \int_{0}^{1}\int_{0}^{v}\left(\frac{(u/v^2)}{1-u}\,\frac{\log{(u/v^2)}}{\log{u}}\right)\,du\,dv = \int_{0}^{1}\int_{\color{red}{0}}^{\color{red}{v}}\left[\frac{u}{1-u}\,\frac{1}{v^2}\left(1-2\frac{\log{v}}{\log{u}}\right)\right]\color{red}{\,du\,dv} \\[3mm] &= \int_{0}^{1}\int_{\color{red}{u}}^{\color{red}{1}}\left[\frac{u}{1-u}\,\frac{1}{v^2}\left(1-2\frac{\log{v}}{\log{u}}\right)\right]\color{red}{\,dv\,du} \quad\qquad\qquad\qquad\qquad\qquad\color{blue}{\{1\}} \\[3mm] &= \int_{0}^{1}\frac{u}{1-u}\,du\,\int_{u}^{1}\left(\frac{1}{v^2}-\frac{2}{\log{u}}\frac{\log{v}}{v^2}\right)\,dv \\[3mm] &= \int_{0}^{1}\frac{u}{1-u}\,du\,\left[-\frac{1}{v}+\frac{2}{\log{u}}\frac{1+\log{v}}{v}\right]_{u}^{1} \qquad\qquad\qquad\qquad\qquad\qquad\color{blue}{\{2\}} \\[3mm] &= \int_{0}^{1}\frac{u}{1-u}\left(\frac{-2}{\log{u}}\frac{1-u}{u}-\frac{1+u}{u}\right)\,du = \int_{0}^{1}\left(\frac{-2}{\log{u}}-\frac{1+u}{1-u}\right)\,du \\[3mm] &= \int_{0}^{1}\left(\frac{-2}{\log{u}}-\frac{1+u\color{red}{-1+1}}{1-u}\right)\,du = \int_{0}^{1}\left(\frac{-2}{\log{u}}+\frac{-2}{1-u}+1\right)\,du \\[3mm] &= \int_{0}^{1}\,du\,-2\int_{0}^{1}\left(\frac{1}{\log{u}}+\frac{1}{1-u}\right)\,du = \color{red}{1 - 2\,\gamma} \quad\qquad\qquad\qquad\qquad\color{blue}{\{3\}} \\[3mm] \end{align} $$

$\,\color{blue}{\{1\}}\colon\,$ Change order integration.
$\,\color{blue}{\{2\}}\colon\,$ IBP: $\,\int\log{x}\,\frac{dx}{x^2},\,\{u=\log{x}\,{\small\Rightarrow}\,du=\frac{dx}{x},\, dv=\frac{dx}{x^2}\,{\small\Rightarrow}\,v=\frac{-1}{x}\},\,=-\frac{\log{x}}{x}+\int\frac{dx}{x^2}=-\frac{1+\log{x}}{x}$.
$\,\color{blue}{\{3\}}\colon\,$ Integral Representation of Euler–Mascheroni Constant: $\quad\gamma = \int_{0}^{1}\left(\frac{1}{\log{x}}+\frac{1}{1-x}\right)\,dx$.

$\endgroup$
2
  • $\begingroup$ @Algebra: Thanks. $\endgroup$ Jan 21, 2017 at 8:31
  • $\begingroup$ No, thanks you for answering the question @Hazem Orabi $\endgroup$ Jan 21, 2017 at 17:55
4
$\begingroup$

$\newcommand{\bbx}[1]{\,\bbox[8px,border:1px groove navy]{\displaystyle{#1}}\,} \newcommand{\braces}[1]{\left\lbrace\,{#1}\,\right\rbrace} \newcommand{\bracks}[1]{\left\lbrack\,{#1}\,\right\rbrack} \newcommand{\dd}{\mathrm{d}} \newcommand{\ds}[1]{\displaystyle{#1}} \newcommand{\expo}[1]{\,\mathrm{e}^{#1}\,} \newcommand{\ic}{\mathrm{i}} \newcommand{\mc}[1]{\mathcal{#1}} \newcommand{\mrm}[1]{\mathrm{#1}} \newcommand{\pars}[1]{\left(\,{#1}\,\right)} \newcommand{\partiald}[3][]{\frac{\partial^{#1} #2}{\partial #3^{#1}}} \newcommand{\root}[2][]{\,\sqrt[#1]{\,{#2}\,}\,} \newcommand{\totald}[3][]{\frac{\mathrm{d}^{#1} #2}{\mathrm{d} #3^{#1}}} \newcommand{\verts}[1]{\left\vert\,{#1}\,\right\vert}$

$\ds{\int_{0}^{1}\int_{0}^{1}{x \over 1 - xy}\, {\ln\pars{x} - \ln\pars{y} \over \ln\pars{x} + \ln\pars{y}}\,\dd x\,\dd y = 1 - 2\gamma\,,\qquad\gamma:\ Euler\mbox{-}Mascheroni\ Constant}$.

\begin{align} &\int_{0}^{1}\int_{0}^{1}{x \over 1 - xy}\, {\ln\pars{x} - \ln\pars{y} \over \ln\pars{x} + \ln\pars{y}}\,\dd x\,\dd y \\[5mm] = &\ \left.\partiald{}{\mu}\int_{0}^{1}\int_{0}^{1}{x \over 1 - xy} \pars{x^{\mu} - y^{\mu}} \bracks{-\int_{0}^{\infty}\pars{xy}^{\,t}\,\dd t}\,\dd x\,\dd y\, \right\vert_{\ \mu\ =\ 0} \\[5mm] = &\ \left.\partiald{}{\mu}\int_{0}^{\infty}\int_{0}^{1}\int_{0}^{1} {x^{t + 1}y^{t + \mu} - x^{t + \mu + 1}y^{t} \over 1 - xy} \,\dd x\,\dd y\,\dd t\,\right\vert_{\ \mu\ =\ 0} \\[5mm] = &\ \left.\partiald{}{\mu}\int_{0}^{\infty}\int_{0}^{1}\int_{0}^{y} {x^{t + 1}y^{\mu - 2} - x^{t + \mu + 1}y^{-\mu - 2} \over 1 - x} \,\dd x\,\dd y\,\dd t\,\right\vert_{\ \mu\ =\ 0} \\[5mm] = &\ \left.\partiald{}{\mu}\int_{0}^{\infty}\int_{0}^{1}\int_{x}^{1} {x^{t + 1}y^{\mu - 2} - x^{t + \mu + 1}y^{-\mu - 2} \over 1 - x} \,\dd y\,\dd x\,\dd t\,\right\vert_{\ \mu\ =\ 0} \\[5mm] = &\ \left.\partiald{}{\mu}\int_{0}^{\infty}\int_{0}^{1} \pars{x^{t + 1}\,{1 - x^{\mu - 1} \over \mu - 1} + x^{t + \mu + 1}\,{1 - x^{-\mu - 1}\over \mu + 1}} {\dd x\,\dd t \over 1 - x}\,\right\vert_{\ \mu\ =\ 0} \\[5mm] = &\ \left.\partiald{}{\mu}\int_{0}^{\infty}\int_{0}^{1} \pars{{1 \over \mu - 1}\,{x^{t + 1} - x^{t + \mu} \over 1 - x} + {1 \over \mu + 1}\,{x^{t + \mu + 1} - x^{t} \over 1 - x}} \dd x\,\dd t\,\right\vert_{\ \mu\ =\ 0} \\[5mm] = &\ \left.\partiald{}{\mu}\int_{0}^{\infty} \bracks{{\Psi\pars{t + \mu + 1} - \Psi\pars{t + 2} \over \mu - 1} + {\Psi\pars{t + 1} - \Psi\pars{t + \mu + 2} \over \mu + 1}} \dd t\,\right\vert_{\ \mu\ =\ 0} \\[5mm] = &\ \left.\partiald{}{\mu}\bracks{% {1 \over \mu - 1}\,\ln\pars{\Gamma\pars{t + \mu + 1} \over \Gamma\pars{t + 2}} + {1 \over \mu + 1}\,\ln\pars{\Gamma\pars{t + 1} \over \Gamma\pars{t + \mu + 2}}} _{\ t\ =\ 0}^{\ t\ \to\ \infty}\, \right\vert_{\ \mu\ =\ 0} \\[5mm] = &\ \partiald{}{\mu}\bracks{% -\,{\ln\pars{\Gamma\pars{\mu + 1}} \over \mu - 1} + {\ln\pars{\Gamma\pars{\mu + 2}} \over \mu + 1}}_{\ \mu\ =\ 0} = \Psi\pars{1} + \Psi\pars{2} = 2\Psi\pars{1} + 1 = \bbx{\ds{1 - 2\gamma}} \end{align}

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.